The Influence of Work-Life Balance on Employee Productivity: A Literature Review in the Context of Modern Companies - Vitaharsa, Leonardo Indra; Wasino, Hadiwiyanto (PT Maju Malaqbi Makkarana, 2025)
Work-life balance (WLB) plays a crucial role in enhancing employee productivity in modern companies. This literature review examines how flexible work policies, stress management, and a healthy organizational culture contribute to work-life balance and their impact on individual and organizational performance. The findings indicate that work flexibility, such as remote work and flexible working hours, improves employee well-being and reduces turnover rates. However, without proper management, technology that supports work flexibility can increase workload and disrupt WLB. Additionally, stress management strategies and inclusive leadership support are key factors in maintaining long-term productivity. Therefore, companies must adopt a holistic approach by integrating WLB policies, mental well-being programs, and a supportive work culture to create an environment that fosters sustainable productivity.